Childhood cigarette and alcohol use: Negative links with adjustment. (November 2016) - Staff, Jeremy; Maggs, Jennifer L.; Cundiff, Kelsey; Evans-Polce, Rebecca J.
Abstract: Children who initiate cigarette or alcohol use early—during childhood or early adolescence—experience a heightened risk of nicotine and alcohol dependence in later life as well as school failure, crime, injury, and mortality. Using prospective intergenerational data from the Millennium Cohort Study (MCS), we investigate the association between early substance use initiation (cigarettes or alcohol) and age 11 school engagement, academic achievement, and wellbeing. The ongoing MCS tracks the development of a nationally representative sample of children in the United Kingdom (born 2000–2002) from infancy through adolescence. At age 11, MCS children (n = 13, 221) indicated whether they had ever used cigarettes or alcohol; at age 7 and 11 they reported on school engagement and wellbeing and completed investigator-assessed tests of academic achievement. Using propensity score methods, children who had initiated cigarette or alcohol use by age 11 were matched to abstaining children with similar risks (or propensities) of early substance use, based on numerous early life risk and protective factors assessed from infancy to age 7. We then examined whether early initiators differed from non-initiators in age 11 adjustment and achievement. Results show that substance use by age 11 was uncommon (3% cigarettes; 13% alcohol). After matching for propensity for early initiation, school engagement and wellbeing were significantly lower among initiators compared to non-initiators. Academic achievement was not consistently related to early initiation. We conclude that initiation of smoking and drinking in childhood is associated with poorer adjustment. Highlights: Childhood substance use carries long-term developmental and health risks. Links of childhood alcohol and cigarette use with adjustment may be spurious. 3% smoked and 13% drank alcohol by age 11 in large nationally representative sample. Early initiators and non-users differ on wide range of early childhood risk factors. Early initiation predicts low age 11 school engagement, wellbeing beyond early risk.